EXTRACT VIRGIN OLIVE OIL AS A NATURAL REMEDY IN REMOVING CRADLE CAP IN INFANTS - Lubis, Kholilah; Wardianti, Nofri (Jurnal Kesehatan - STIKes Prima Nusantara, 2021)
Background: Cradle cap (Infantile Seborrhoeic Dermatitis), a form of dermatitis that manifested as patches of scale severity on the scalp of infants. The plaque is hard, thickness and tightly scale accompanied by red inflammation resembling a hat, cause itching, discomfort and causes stress to the parents with the prevalence rate of 3.5% in worldwide distribution. Extract Virgin Olive Oil (EVOO) have an anti-inflammatory, antioxidant, wound healing, skin ageing, and reduces the incidence of skin cancer.Purpose: The aim to determine the effect of EVOO with a duration time to recover the cradle cap.Method: This study was a queasy experiment with the control group (was not administration) and the intervention group (was given four drops of EVOO). The population was 21 infants and only five infants with cradle caps in the Siulak Mukai Public Medical Centre area, Kerinci Regency, Jambi. The sampling technique used the purposive sampling technique for as many as 10 samplings. Infants are aged 1-4 months; cradle cap confirmed in the head with a low degree (less than 10%) from the infant's head's frontal area and parietal areas. The statistical analysis used an independent sample t-test.Result: There were significant differences between the two groups in the duration of recovered the cradle cap (p = 0.000). Further analysis demonstrated a favourable effect of the intervention group with duration time to recovered 10.20 days than the control group is 27.60 days.Conclusion: EVOO is recommended to remove cradle caps in infants and nourish hair by making the infant's scalp moist by preventing oxidative damage.